IoT Based Carbon Monoxide Monitoring and Warning System Application in Vehicles - Razemi, Muhammad Alif; Nor Surayahani Suriani (Evolution in Electrical and Electronic Engineering, 2024)
Nowadays, frequent incidents occur of poisoning of carbon monoxide gas inside cars, with most of the reported cases resulting in death. The goal of this work is to create and improve existing systems related to carbon monoxide leaks to alert the car user, monitor carbon monoxide levels, and ventilation support in car cabins. The system includes a gas sensor to identify the level of carbon monoxide gas, at which instance a control action is taken MQ-7 sensor was implemented as the carbon monoxide sensor in the system. The carbon monoxide level can be monitored on LCD and mobile phones that display on Virtuino IoT applications. When the carbon monoxide reading reaches the threshold level, the buzzer will ring and if the user does not reset the system, the system will open the car window and immediately send the SMS of the car location to emergency contact. A test was conducted on two types of cars with different car sizes to test the system response. The results show that the small car size will respond slightly faster than the larger car size. The time response between the two types of cars is acceptable and still in safe range. These implementations of this work imply that this technology has the potential to reduce the tragedies that occur of poisoning of carbon monoxide gas inside of cars by providing monitoring, alerting, and ventilation support that allows people to be in safe conditions in car cabins.